2022
DOI: 10.1007/s11135-022-01434-5
|View full text |Cite
|
Sign up to set email alerts
|

Sri Lankans’ residential segregation and spatial inequalities in Southern Italy: an empirical analysis using fine-scale data on regular lattice geographies

Abstract: Sri Lankans constitute one of Italy's oldest foreign communities. A comparative geographic study of Sri Lankans’ settlement patterns in three main municipalities of South Italy (Naples, Palermo, and Catania) is performed in the present work. The uniqueness of the analysis relies on the fact that, to the authors’ knowledge, no other existing studies comparatively examine the spatial segregation of Sri Lankan communities in different southern European municipalities. Moreover, implementing a single geographic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Thereafter, Italy's easier admission possibilities compared to other European countries, its simplified procedure for family reunifications and its use of socalled nominative calls (formal requests made by an Italian employer guaranteeing a job to a foreigner) attracted a large number of Sri Lankan men, balancing the proportions between genders (Henayaka-Lochbihler & Lambusta, 2004). As mentioned above, Sri Lankans' spatial distribution across Italy is characterized by a twofold specificity 1 (Benassi et al, 2023a). First, Sri Lankans prefer to settle in large cities, 2 particularly those listed in Table 1, which were home to almost 55% of the total number of Sri Lankans residing in Italy at the beginning of 2021 (as indicated by the bold numbers in the fourth and ninth columns of Table 1).…”
Section: Sri Lankans In Italymentioning
confidence: 99%
See 2 more Smart Citations
“…Thereafter, Italy's easier admission possibilities compared to other European countries, its simplified procedure for family reunifications and its use of socalled nominative calls (formal requests made by an Italian employer guaranteeing a job to a foreigner) attracted a large number of Sri Lankan men, balancing the proportions between genders (Henayaka-Lochbihler & Lambusta, 2004). As mentioned above, Sri Lankans' spatial distribution across Italy is characterized by a twofold specificity 1 (Benassi et al, 2023a). First, Sri Lankans prefer to settle in large cities, 2 particularly those listed in Table 1, which were home to almost 55% of the total number of Sri Lankans residing in Italy at the beginning of 2021 (as indicated by the bold numbers in the fourth and ninth columns of Table 1).…”
Section: Sri Lankans In Italymentioning
confidence: 99%
“…Sri Lankans exhibit a strong work specialization in the domestic sector, with their most common jobs being domestic assistance, housekeeping and cleaning services (Benassi et al, 2023a;Mazza & Punzo, 2016;Mazza et al, 2018). In particular, many live in the house in which they work (Henayaka-Lochbihler & Lambusta, 2004).…”
Section: Sri Lankans In Italymentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are fewer contributions focused on the Italian context compared to the ones regarding Northern Europe, the relevance of this topic has been rapidly increasing, leading to a growing number of analyses (Benassi et al 2023b(Benassi et al , 2019Bitonti et al 2023;Busetta et al 2015;Mazza et al 2018;Mazza and Punzo 2016;Petsimeris and Rimoldi 2015;Rimoldi and Terzera 2017). Overall, these studies have revealed a spatial dichotomy at the macro level between the northern and southern parts of Italy, with Northern Italy exhibiting a higher proportion of immigrants and experiencing lower levels of residential segregation and inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we believe that the assessment of possible betweencity variations in segregation could encourage the critical thinking of the implications of macro-level dynamics on the immigrants' residential allocation choices. Furthermore, the comparative approach implemented here allows the present work to cope with the scarcity of segregation studies (e.g., Benassi et al 2023b), performing comparative analyses across Italian cities. The basic reasoning is to analyse several dimensions of segregation starting with the traditional separation between the dominant group (i.e., Italians) and the minority ones (the main immigrant groups residing in the areas), and then moving to the analysis of multi-group separation and interaction in the perspective of a growing "super-diversity" of the society.…”
Section: Introductionmentioning
confidence: 99%